Das Siebenstromland zwischen Bronze- und Früheisenzeit eine Regionalstudie - Gass, Anton (De Gruyter, 2016)
"The southeastern Land of Seven Rivers (Kazakhstan)--a small region in the Eurasian steppes--shows an enormous concentration of Bronze and early Iron Age archeological monuments, only a small fraction of which have been described by researchers. This study, the first comprehensive investigation of these monuments, also makes an important contribution to knowledge about the historical-cultural evolution of the region"--Publisher's website
1602
Keywords: Archéologie des steppes; Archéologie sociale; Fouilles (Archéologie); Monuments; Antiquities; Bronze age; Excavations (Archaeology); HISTORY / Ancient / General; Iron age; Nomads; Social archaeology; Social change; Steppe archaeology; Bronze age -- Kazakhstan; Excavations (Archaeology) -- Kazakhstan; Iron age -- Kazakhstan; Monuments -- Kazakhstan; Nomads -- Kazakhstan -- History -- To 1500; Social archaeology -- Kazakhstan; Social change -- Kazakhstan -- History -- To 1500; Steppe archaeology -- Kazakhstan; Eisenzeit; Bronzezeit; Gräberfeld; Siebenstromland; Kurgan; To 1500; Kazakhstan / Antiquities; Kazakhstan / Antiquités; Kazakhstan; Electronic book; Electronic books; History; Hochschulschrift